2013
DOI: 10.3109/13880209.2012.747545
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of phycocyanin: Effects on KKAy mice

Abstract: Context: Phycocyanin (PC) has been proven to have many therapeutic properties, but its effects on diabetes have not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 26 publications
(23 reference statements)
2
41
0
Order By: Relevance
“…Moreover, numerous biological effects of C-PC have been reported, such as anti-inflammatory [7], anti-apoptotic [8], antioxidant [9], and hypolipidemic [10] activities. In addition, the literature provides some evidence on the in vivo hypoglycemic activity exerted by C-PC peptides in different animal models [11,12]. In particular, a recent study has shown that C-PC peptides activate the insulin signaling pathway and glucokinase expression in the pancreas and liver of diabetic mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous biological effects of C-PC have been reported, such as anti-inflammatory [7], anti-apoptotic [8], antioxidant [9], and hypolipidemic [10] activities. In addition, the literature provides some evidence on the in vivo hypoglycemic activity exerted by C-PC peptides in different animal models [11,12]. In particular, a recent study has shown that C-PC peptides activate the insulin signaling pathway and glucokinase expression in the pancreas and liver of diabetic mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that it has antioxidant activity against hydroxyl radicals, peroxide radicals, and DPPH radicals, and it has been used as an anti‐tumor and anti‐inflammatory agent due to its hepatoprotective properties . Finally it has potential activity against diabetes, and hypertension …”
Section: Introductionmentioning
confidence: 99%
“…With respect to the role of NADPH oxidase activation in the genesis of metabolic syndrome and type 2 diabetes, studies with rodent models of these syndromes report favorable effects of oral phycocyanin or whole spirulina on glycemic control, serum lipid profile, blood pressure, and steatohepatitis [91,92,93,94,95,96]. Also, two clinical trials, in which spirulina was administered (likely in suboptimal doses) to type 2 diabetics, likewise found modest improvements in these parameters [97,98].…”
Section: Phycocyanobilin: a Nutraceutical Inhibitor Of Nadph Oxidasementioning
confidence: 99%